Pendampingan Penyusunan LKPS dan LED Program Studi di Lingkungan FKIP sebagai Syarat Re-Akreditasi - Arifuddin Arifuddin; Arjudin Arjudin; Jamaluddin Jamaluddin; A. A. Sukarso; Edy Kurniawansyah; Mohammad Archi Maulyda (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2021)
LKPS and LED mentoring activities are one of the duties and responsibilities of the Faculty Quality Assurance Unit (GPMF). The study programs that will participate in the mentoring activities are the Civics Education Study Program, the PGSD Study Program, and the Physics Education Study Program. The activity implementation method consists of 3 stages as follows: (1) Coordination meeting; (2) Implementation of Mentoring; and (3) Evaluation of Mentoring Activities. Assistance activities are carried out periodically within a period of 3 weeks. Each study program will be accompanied by 2 GPMF members. Based on the identified outcomes, the percentage of achievement of the outcomes is 66.67%. This calculation is obtained from the number of completed outputs. The PPKn study program cannot complete the LKPS and LED, while the PGSD and Physics Education study programs can complete the LKPS and LED.